Thermal Properties of Alpha Decay in Magnetic Field Medium - Nwabuzor, P. O.; Ngiangia, A. T.; George, F. J. (Atom Indonesia, 2025)
An analytical study of alpha decay in the presence of an imposed magnetic field and some of its thermodynamic properties was considered. The study used the JWKB method to determine the allowed energy eigenvalues and mean lifetime of the decay process with the understanding that the two expressions will enable us to determine the impact of the imposed magnetic field and the select thermodynamic properties. The study reveals that the solution admits a discrete energy spectrum and the radial wave function decreases exponentially as the imposed magnetic field decreases and is square integrable with zero point energy and the presence of the imposed magnetic field, enhanced the decay rate of the particles as well as partially removed the degeneracy of the process. The four thermodynamic properties considered as shown in the graphs plotted also laid credence by enhancing the entropy and the Helmholtz free energy, while the internal energy and the specific heat at constant volume of the decay process, depreciated as the magnetic field increases as well as attainment of saturation point. Generally, the shape of the wave function plot confirmed the radioactive decay curve.